INFLUENCE OF BODY WEIGHT ON SEMEN CHARACTERISTICS IN SURTI BUCKS - ATARA, F B; CHAUDHARI, C F; CHAUDHARY, M M; MODI, L C; CHAUDHARI, N F; KHASATIYA, C T; BHOI, D B (The Indian Journal of Animal Reproduction, 2022)
Semen samples were collected by artificial vagina method twice in a week from nine Surti bucks.The ejaculateswere divided in to three groups based on the body weight of bucks viz.,G1-up to 30 kg (n=112); G2-30.1 to 40 kg(n=98) andG3 - above 40 kg (n=78). Mean density was significantly (P
Keywords: Artificial vagina; Body weight; Buck; Motility degeneration rate; Semen parameters